Metabolic Control and Illness Perceptions in Adolescents with Type 1 Diabetes. (22nd November 2015) - Wisting, Line; Bang, Lasse; Natvig, Henrik; Skrivarhaug, Torild; Dahl-Jørgensen, Knut; Lask, Bryan; Rø, Øyvind
Abstract : Background . Disturbed eating behavior and psychosocial variables have been found to influence metabolic control, but little is known about how these variables interact or how they influence metabolic control, separately and combined. Objective . To explore associations between metabolic control (measured by HbA1c) and eating disorder psychopathology, coping strategies, illness perceptions, and insulin beliefs in adolescents with type 1 diabetes. Methods . A total of 105 patients (41.9% males) with type 1 diabetes (12–20 years) were interviewed with the Child Eating Disorder Examination. In addition, self-report psychosocial questionnaires were completed. Clinical data, including HbA1c, was obtained from the Norwegian Childhood Diabetes Registry. Results . Significant gender differences were demonstrated. Among females, HbA1c correlated significantly with eating restriction (.29, p < .05), the illness perception dimensions consequences, personal control, coherence, and concern (ranging from .33 to .48), and the coping strategy ventilating negative feelings (−.26, p < .05). Illness perception personal control contributed significantly to HbA1c in a regression model, explaining 23% of the variance among females ( β .48, p < .001). None of the variables were significantly associated with HbA1c among males. Conclusions . Illness perceptions appear to be important contributors to metabolic control in females, but not males, with type 1 diabetes.